Dietary Supplementation with Vitamin E in Hyperlipoproteinemias: Effects on Plasma Lipid Peroxides, Antioxidant Activity, Prostacyclin Generation and Platelet Aggregability - Szczeklik, A; Gryglewski, R J; Domagala, B; Dworski, R; Basista, M (Thrombosis and Haemostasis, 1985)
In a placebo-controlled trial healthy volunteers and patients with hyperlipoproteinemias types II and IV received orally vitamin E at doses of 300 mg and 600 mg daily for 2 weeks. Serum tocopherol levels increased two-fold, but serum concentrations of total lipids, cholesterol, triglycerides, ceruloplasmin and transferrin remained unchanged. Dietary supplementation with vitamin E suppressed elevated concentrations of plasma lipid peroxides and this effect was correlated with an increase in serum antioxidant activity. In patients a mild platelet suppressant effect of vitamin E (600 mg daily) was observed.Feeding an atherogenic diet to rabbits for a week resulted in elevation of plasma lipid peroxides and a 90% decrease in arterial generation of prostacyclin. Enrichment of the atherogenic diet with 100 mg vitamin E daily prevented the increase in plasma lipid peroxides and protected the prostacyclin generating system in arteries. Thus, in hyperlipoproteinemias vitamin E corrects certain abnormalities of lipid metabolism which might predispose to atherosclerosis.
Keywords: Vitamin E; Hyperlipoproteinemias; Lipid peroxides; Prostacyclin; Atherosclerosis